2019
DOI: 10.1177/0269881119827815
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic effects on inhibitory control depend on the interplay of prior task experience and working memory demands

Abstract: Background: Catecholamines affect response inhibition, but the effects of methylphenidate on inhibitory control in healthy subjects are heterogenous. Theoretical considerations suggest that working memory demands and learning/familiarization processes are important factors to consider regarding catecholaminergic effects on response inhibition. Aims: The purpose of this study was to examine the role of working memory demands and familiarization for methylphenidate effects on response inhibition. Methods: Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
(116 reference statements)
4
22
0
Order By: Relevance
“…Regarding the level of familiarity of the task performed, besides the possibility that this effect may arise from better ability to extract salient information (Krueger 1975), several lines of evidence using pharmacological modulations targeting the noradrenergic and dopaminergic system have shown that the effects of the pharmacological modulation depend on learning performance or prior task experience (Adelhöfer et al 2019;Bensmann et al 2019;Mückschel et al 2020a, b). It has been argued that learning/prior task experience and actions of the noradrenergic/dopaminergic system tap into similar mechanisms or principles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the level of familiarity of the task performed, besides the possibility that this effect may arise from better ability to extract salient information (Krueger 1975), several lines of evidence using pharmacological modulations targeting the noradrenergic and dopaminergic system have shown that the effects of the pharmacological modulation depend on learning performance or prior task experience (Adelhöfer et al 2019;Bensmann et al 2019;Mückschel et al 2020a, b). It has been argued that learning/prior task experience and actions of the noradrenergic/dopaminergic system tap into similar mechanisms or principles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that learning/prior task experience and actions of the noradrenergic/dopaminergic system tap into similar mechanisms or principles. This common neural principle likely refers to 'gain control' mechanisms (Bensmann et al 2019). Gain control is a general working principle in neural networks found at sensory, cognitive (Adelhöfer et al 2018;Salinas and Thier 2000;Servan-Schreiber et al 1990;Beste et al 2016), and motor levels (Greenhouse et al 2015;Thura and Cisek 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Without the use of a perceptual learning protocol, a decline in inhibition performance occurs when the task is executed for the second time likely because the repetition is amplifying the automation of the response tendency triggered by more frequent GO stimuli compared to NOGO stimuli (Dippel et al, ). The tendency to respond to GO stimuli is assumed to automate with an increase in task experience (Bensmann, Zink, Roessner, Stock, & Beste, ; Dippel et al, ; Dippel, Chmielewski, Mückschel, & Beste, ; Helton, ). The perceptual learning protocol, however, seems to have a “protective effect” since repeated task administration that likely induces a prepotent tendency to respond did not modulate response inhibition performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is mounting evidence that the effects of MPH depend on the level of prior experience or familiarity with a given task ( Bensmann et al, 2019 ; Mückschel et al, 2020a , 2020b ). These insights have been gained through the use of cross-over study designs.…”
Section: Introductionmentioning
confidence: 99%